2002
DOI: 10.1086/343789
|View full text |Cite
|
Sign up to set email alerts
|

Population Synthesis in the Blue. II. The Spectroscopic Age of 47 Tucanae

Abstract: We develop a new set of models for intermediate-metallicity single stellar populations in the blue/optical region and use those models to determine the spectroscopic age of 47 Tuc. The models are based on a moderately high-resolution (1.8Å FWHM) empirical spectral library, state-of-the-art theoretical isochrones from M. Salaris and the most recent set from the Padova group, and new semiempirical calibrations between fundamental stellar parameters and observables. Model line-strengths include all corrections fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 34 publications
(63 reference statements)
1
59
0
Order By: Relevance
“…Some solutions have been proposed, such as the inclusion of atomic diffusion in the stellar evolutionary models or the use of α-enhanced isochrones (see Vazdekis et al 2001), although none of these have been implemented in publicly available stellar population models. Schiavon et al (2002) showed, for the particular case of 47Tuc, that the luminosity function of the red giant branch is underestimated in the stellar evolutionary models and that the use of the observed luminosity functions instead of theoretical ones results in derived ages for this cluster consistent with the age of the Universe and with those derived directly from the colour-magnitude diagram. A similar effect in super-solar metallicity models would cause spectroscopic ages to be 30% too high (see Schiavon et al 2002, for details).…”
Section: Figmentioning
confidence: 62%
“…Some solutions have been proposed, such as the inclusion of atomic diffusion in the stellar evolutionary models or the use of α-enhanced isochrones (see Vazdekis et al 2001), although none of these have been implemented in publicly available stellar population models. Schiavon et al (2002) showed, for the particular case of 47Tuc, that the luminosity function of the red giant branch is underestimated in the stellar evolutionary models and that the use of the observed luminosity functions instead of theoretical ones results in derived ages for this cluster consistent with the age of the Universe and with those derived directly from the colour-magnitude diagram. A similar effect in super-solar metallicity models would cause spectroscopic ages to be 30% too high (see Schiavon et al 2002, for details).…”
Section: Figmentioning
confidence: 62%
“…It is easy to see from these outputs that our results imply that 20−30% of the stars have ages older than the most recent estimates of the age of the Universe. This is a well known problem in the stellar population models (e.g., Vazdekis et al 2001;Schiavon et al 2002;Maraston et al 2011, V10). Several possible solutions have been proposed to alleviate this so-called zero point problem, and, in fact, several groups have successfully reconcile the age of globular clusters with ΛCDM cosmology (see Krauss & Chaboyer 2003); Percival & Salaris (2009) showed that systematic uncertainties associated with the three fundamental stellar atmospheric parameters might have a non negligible impact on the resulting SSP line-strengths.…”
Section: Star Formation Historiesmentioning
confidence: 98%
“…For example, the use of Padova (Girardi et al 2000; which are those used by V10) gives older ages than Padova (Bertelli et al 1994). Schiavon et al (2002) also stressed the importance of correctly modelling the luminosity function at the level of the giant branch for the particular problem of globular clusters. He showed, for 47 Tuc, that if the observed luminosity function is used rather than the theoretical ones, the spectroscopic and the colour-magnitude diagram ages coincide and are lower than the age of the Universe.…”
Section: Star Formation Historiesmentioning
confidence: 99%
“…The absolute value of the age depends on the methodology, a wellknown issue plaguing most stellar population studies (see, e.g., Vazdekis et al 2001;Schiavon et al 2002). Throughout this work, we adopt as a reference the age estimates from spectral fitting (method F IT 1 above), rescaled to match the Hγ275-based value (∼ 11 Gyr) at the galaxy centre.…”
Section: Radial Profiles Of Age and Metallicitymentioning
confidence: 99%